Settlement Mechanisms of agricultural lands that are subject of reclamation in the framework of the promotion of investment in Algeria - KHELIFI, Chaouki (Journal of Human Sciences, 2020)
In this research we’re discussing the legal mechanisms relating to the regularization of agricultural land in the framework of the promotion of investment, in Algeria, and in it wetry to analyze the modalities and the procedures of regularization of the agricultural lands to bereclaimed, in the framework of the law n ° 83/18 of13/08/1983 relating to the possession of agricultural land ownership , as well as those procedures and modalities for the regularization of the agricultural land attributed within the framework of the investment, according to theinterministerial circular No 750 of 18/07/2018. Finally, we will try to determine the effectiveness of those procedures, with the aim of bring out the suggestions that must be submitted to the legislation and regulations in effect, relating to the settlement of agricultural lands that are the subject of reclamation in the framework of the investment.